2003
DOI: 10.1097/01.crd.0000078443.08887.28
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Aortic Dissection in Marfan???s Syndrome: Possible Effects of Anticoagulation

Abstract: Recent reports support the role of a valve-sparing procedure in ascending aortic dissection in patients with Marfans syndrome. A 49-year-old woman with Marfans syndrome and prior aortic aneurysm repaired with a composite graft presented with sudden-onset chest pain. Following an initial negative computed tomographic (CT) scan, a long dissection involving the descending thoracic and abdominal aorta was discovered on a repeat CT scan a few hours later. Symptoms improved gradually with optimal medical management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Bradbury et al performed a case record review of 65 AAA patients and found a direct correlation between platelet count on admission to the hospital and death after emergency repair of ruptured AAA [16]. Recent studies also demonstrate that anticoagulants might be responsible for a prolonged healing process and adverse clinical events including recurrence and rupture in the treatment of aortic dissection [12], [13], [14]. Given these inconsistent results, we investigated the effects of platelets inhibition on AAA initiation and progression and its mechanistic link using human AAA samples and the murine Ang II–infusion model of AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradbury et al performed a case record review of 65 AAA patients and found a direct correlation between platelet count on admission to the hospital and death after emergency repair of ruptured AAA [16]. Recent studies also demonstrate that anticoagulants might be responsible for a prolonged healing process and adverse clinical events including recurrence and rupture in the treatment of aortic dissection [12], [13], [14]. Given these inconsistent results, we investigated the effects of platelets inhibition on AAA initiation and progression and its mechanistic link using human AAA samples and the murine Ang II–infusion model of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al found that platelet activation was involved in progression of AAA [11]. However, clinical studies demonstrated that anticoagulants might lead to adverse clinical events including recurrence and rupture in the treatment of aortic dissection [12], [13], [14]. Therefore, the releationship between platelets and AAA progression remain unclear [11], [12], [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some physicians suppose that warfarin increases the risk of aortic rupture (6), accelerates progression of dissection (7), and prevents aortic healing by hindering false lumen thrombosis (8). Other physicians presume that warfarin anticoagulation is likely to improve long-term survival of AAAD because it may prevent malperfusion or because it may avoid partial thrombosis of the false lumen (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of false lumen thrombosis was also found to be frequent in those with lower BMI and/or BSA; which was consistent with the results of Reeger et al [20] Recent literature has suggested that oral anticoagulation associated with mechanical valve surgeries or any other interventions may have an effect over FLP. [22,25,26] In a study published in 2007, Gariboldi et al [25] reported higher probability of FLP in patients who took anticoagulant medication postoperatively. The authors stated that these were the results of univariable analysis; however multivariable analysis revealed no correlation between oral anticoagulation and FLP.…”
Section: Discussionmentioning
confidence: 99%